Advances in NKG2D ligand recognition and responses by NK cells. Issue 3 (21st January 2014) - Le Bert, Nina; Gasser, Stephan
Abstract : The natural killer (NK) group 2 member D (NKG2D) is an activating immune receptor expressed on NK cells, cytotoxic T cells and a subset of other T cells. It has an important role in the recognition and lysis of a variety of infected and tumor cells. Despite significant gains in our understanding of NKG2D, the relevance of NKG2D and its ligands in human diseases has only recently started to emerge. Here, we present an overview of the recent advances in NKG2D biology, discuss the expression of NKG2D ligands in cancer patients and evaluate the diagnostic and prognostic potential of NKG2D ligands. Abstract : The March 2014 issue contains a Special Feature on NK cell recognition of unconventional ligands . Natural Killer (NK) cells are bone marrow derived lymphocytes capable of mediating rapid effector responses following pathogen detection in mammals. The name "Natural Killer" derives from the ability of these cells to spontaneously lyse a large range of leukemia cell lines in vitro without prior sensitization. The reviews included in this Special Feature of Immunology and Cell Biology highlight the multifaceted roles of NK cells in detecting unconventional ligands and countering a large range of pathogens and malignancies. Covering a range of topics, including the way adhesion molecules and activating receptors are central to NK cell recognition of their targets, the reviews also highlight some of the challenges that lie ahead in harnessing NK cell function and advancing NK cell immunotherapy strategies to persistent infection, cancer and bone marrow transplantation. Immunology and Cell Biology thanks the coordinator of this Special Feature – Nicholas Huntington – for his planning and input. Further background information on this important topic is available through the accompanying web focus which links to related articles from across Nature Publishing Group.